Lexical And Semantic Features Of Idioms In Modern English And Uzbek Languages (Eurasian Journal of Research, Development and Innovation, 2024)
This article explores the lexical and semantic features of idioms in Modern English and Uzbek, examining how they reflect cultural, historical, and social values. It highlights the fixed structure of idioms, the use of archaic words, and the unique imagery rooted in cultural symbolism in both languages. The semantic analysis underscores the non-literal meaning of idioms, their dependence on cultural context for interpretation, and the role of cultural connotations in shaping their meaning